Model fitting for biodiesel yield analysis from crude palm oil (CPO) - Kabbashi, Nassereldeen; Alam, Md. Zahangir (2010)
This project involves the transesterification reaction of crude palm oil (CPO) to obtain palm oil biodiesel (POB). Five factors have been considered in the experimental design, namely reaction temperature, reaction time, agitation speed, molar ratio of methanol:CPO and Dosage of KOH. The factors were observed by assigning them to each level to study the conversion of crude palm oil (CPO) to palm oil methyl ester which is our biodiesel. This was carried by finding the optimal values of reaction time, 60 min, reaction temperature, 60 ºC, agitation speed, 250 rpm, molar ratio of methanol-to-oil, 10:1 (m/m), and dosage of the catalyst, 1.4 (%wt). Other experimental design and analytical tests were conducted including: density of POB at room temperature, 0.8498 kg l-1, surface tension at STP of 26.96 mN m-1, with Huh-Mason correction of 0.1, and finally free fatty acid percentage of 0.12% (equivalent to acid value of 0.26 mg KOH g-1). The quadratic sum of squares with F-value equals to 264.16 R-squared value the closest to unity 0.9978, also analysis of variance (ANOVA) has been carried out and it is found that the most significant value between all factors is the agitation speed (C) with F-value less than 1 x10-4. Polynomial regression of the quadratic model generated by the optimization software, The table above also shows that run #22 gives the highest actual yield of POME production and with the theoretical yield expected to be 93.573%. Most of the parameters are considered significant (Probability > F value is less than 0.1 or much better 0.05) except for the main factor of molar ratio methanol:CPO (D) which it probability associated of F-value is equal to 0.2553 (> 0.05) so the analysis will consider it unreliable reference to POME yield optimization.